Effects of Surfactant on Flow Boiling Heat Transfer of Ethylene Glycol/Water Mixtures in a Minitube. Issue 13 (21st September 2016) - Feng, Zhaozan; Wu, Zan; Li, Wei; Sundén, Bengt
Abstract : This study investigated effects of surfactant sodium dodecylbenzene sulfonate (SDBS) on flow boiling heat transfer of ethylene glycol/water mixtures in a vertical minitube. Experiments were performed using solutions containing 300 ppm by weight of surfactant and the results were compared with those of pure mixture. Local heat transfer coefficient was measured and found to be dependent on the mass quality. Although the surfactant intensifies the vaporization process, it doesn't necessarily enhance the heat transfer coefficient. Heat transfer coefficients were compared at two different mass fluxes, and the results might be explained based on the local flow pattern and the heat transfer mechanism. After a critical quality, higher quality tends to deteriorate heat transfer due to intermittent dryout, and therefore adding a surfactant to generate more vapor may be of negative effect on the flow boiling heat transfer in a minitube, which is contrary to the experience of enhancing nucleate pool boiling heat transfer with trace surfactants.